Pengaruh Edukasi Pembidaian Terhadap Keterampilan Masyarakat Dalam Memberikan Pertolongan Pertama Cedera Muskuloskeletal Di Desa Wakat - Yanti Tongka; Faradilla M. Suranata; Suwandi I. Luneto (Vitamin : Jurnal ilmu Kesehatan Umum, 2023)
Splinting is a method of first aid in injury/trauma musculoskeletal system. Which useful for health (immobilization) the part of our body that has been injured. By using a tool. This splinting purpose to reduce and relieve pain, prevent the occurrence of bone fracture movements that can cause damage to surrounding soft tissues. The purpose of this study was to determine the effect of splinting education on community skills in providing first aid for musculoskeletal injuries in wakat village objectiveThis study is a quasi – experimental research with a one group pretest-posttest design. Total sampe/sampling 20 people by using the total sampel Sampling technique. Data collection using observation sheet. Analyzed with Mc. Nemar statistical test. Then,the data that has been collected is processed using computer assistance SPSS 16,0 program version From the result Wilcokson statistical test showed that there was a significant influence between education and community skills in providing first aid for musculoskeletal injuries in wakat village, (p)=0,000:a= 0,05 Conclusion in this study there is an influence of splinting education to the skillis of the community in providing first aid Musculoskeletal injuries in wakat village. The results of this study are expected to be able to become a reference for health and education installations in an effort to provide the influence of splinting education on community skills in providing first aid musculoskeletal injures.